New Oxazolidinones for Tuberculosis: Are Novel Treatments on the Horizon? - Chen, Ricky Hao; Burke, Andrew; Cho, Jin-Gun; Alffenaar, Jan-Willem; Davies Forsman, Lina (Pharmaceutics, 2024)
Multidrug-resistant tuberculosis (MDR-TB) is a global health concern. Standard treatment involves the use of linezolid, a repurposed oxazolidinone. It is associated with severe adverse effects, including myelosuppression and mitochondrial toxicity. As such, it is imperative to identify novel alternatives that are better tolerated but equally or more effective. Therefore, this review aims to identify and explore the novel alternative oxazolidinones to potentially replace linezolid in the management of TB. The keywords tuberculosis and oxazolidinones were searched in PubMed to identify eligible compounds. The individual drug compounds were then searched with the term tuberculosis to identify the relevant in vitro, in vivo and clinical studies. The search identified sutezolid, tedizolid, delpazolid, eperezolid, radezolid, contezolid, posizolid and TBI-223, in addition to linezolid. An additional search resulted in 32 preclinical and 21 clinical studies. All novel oxazolidinones except posizolid and eperezolid resulted in positive preclinical outcomes. Sutezolid and delpazolid completed early phase 2 clinical studies with better safety and equal or superior efficacy. Linezolid is expected to continue as the mainstay therapy, with renewed interest in drug monitoring. Sutezolid, tedizolid, delpazolid and TBI-223 displayed promising preliminary results. Further clinical studies would be required to assess the safety profiles and optimize the dosing regimens.